1972
DOI: 10.1016/s0140-6736(72)92259-3
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response Related to Hl-a Antigens in Hodgkin's Disease and Other Lymphomas

Abstract: Alpha-1-antitrypsin levels in controls, autistic children, and children with untreated and with treated cceliac disease. protecting tissues against enzymatic attack, and its serum level does rise as part of an inflammatory response.4 It is possible that a low level of alpha-1-antitryp sin may predispose to the small-intestinal damage which occurs in cceliac disease. It is more difficult to speculate concerning the significance of a reduction in serum alpha-1-antitrypsin in 8 autistic children, none of whom had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1973
1973
1985
1985

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Conclusive data from mice, rats and guinea pigs, and several indications in other species including man have demonstrated that the major histocompatibility system is closely associated with genetic regulation of a number of immune responses [3,4,6,7,12,14,19,23,25,31,33]. The data were mostly elaborated in mice, where a specific genetic locus, Ir-1, was defined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conclusive data from mice, rats and guinea pigs, and several indications in other species including man have demonstrated that the major histocompatibility system is closely associated with genetic regulation of a number of immune responses [3,4,6,7,12,14,19,23,25,31,33]. The data were mostly elaborated in mice, where a specific genetic locus, Ir-1, was defined.…”
Section: Introductionmentioning
confidence: 99%
“…These data however, need further verification. It has been observed that the titre of natural anti-B and the antibody response to iduenza A virus is associated with antigen HL-A 12 [33]. In a recent abstract, BUCKLEY etai.…”
Section: Introductionmentioning
confidence: 99%
“…These data however, need further verification. It has been observed that the titre of natural anti-B and the antibody response to influenza A virus is associated with antigen HL-A12 [33]. In a recent abstract, Buckley et al [7], indicate by family studies that several parameters, such as antibacterial antibodies and differences in immunoglob ulin levels, segregate together with certain HL-A haplotypes.…”
Section: Introductionmentioning
confidence: 99%